Involvement of chemokine receptor CXCR3 in the defense mechanism against Neospora caninum infection in C57BL/6 mice - Hanan H. Abdelbaky; Shuichiro Mitsuhashi; Kenichi Watanabe; Nanako Ushio; Miku Miyakawa; Hidefumi Furuoka; Yoshifumi Nishikawa (Frontiers in Microbiology, 2023)
C-X-C motif chemokine receptor 3 (CXCR3) is an important receptor controlling the migration of leukocytes, although there is no report regarding its role in Neospora caninum infection. Herein, we investigated the relevance of CXCR3 in the resistance mechanism to N. caninum infection in mice. Wild-type (WT) C57BL/6 mice and CXCR3-knockout (CXCR3KO) mice were used in all experiments. WT mice displayed a high survival rate (100%), while 80% of CXCR3KO mice succumbed to N. caninum infection within 50 days. Compared with WT mice, CXCR3KO mice exhibited significantly lower body weights and higher clinical scores at the subacute stage of infection. Flow cytometric analysis revealed CXCR3KO mice as having significantly increased proportions and numbers of CD11c-positive cells compared with WT mice at 5 days post infection (dpi). However, levels of interleukin-6 and interferon-γ in serum and ascites were similar in all groups at 5 dpi. Furthermore, no differences in parasite load were detected in brain, spleen, lungs or liver tissue of CXCR3KO and WT mice at 5 and 21 dpi. mRNA analysis of brain tissue collected from infected mice at 30 dpi revealed no changes in expression levels of inflammatory response genes. Nevertheless, the brain tissue of infected CXCR3KO mice displayed significant necrosis and microglial activation compared with that of WT mice at 21 dpi. Interestingly, the brain tissue of CXCR3KO mice displayed significantly lower numbers of FoxP3+ cells compared with the brain tissue of WT mice at 30 dpi. Accordingly, our study suggests that the lack of active regulatory T cells in brain tissue of infected CXCR3KO mice is the main cause of these mice having severe necrosis and lower survival compared with WT mice. Thus, CXCR3+ regulatory T cells may play a crucial role in control of neosporosis.